Performance analysis of distributed Alamouti space-time codes in full-duplex cooperative communication system - Wen-jiang FENG; Guo-ling LIU; Xin-hui ZHONG; Chu-nan YAO; Bo-wei ZHANG; Cai-li DAI (Tongxin xuebao)
The error performance of distributed Alamouti space-time code (DASTC) was investigated in a 3-node full-duplex (FD) cooperative communication system with the presence of residual self-interference (RSI).Based on the asymptotic expression of the pairwise error probability in the high transmit power region,the diversity and coding gain were derived.The impact of residual self-interference on the construction of space-time code was analyzed and the achievable condition of diversity gain was obtained.Analytical results show that DASTC achieves full rate and full diversity in the FD cooperative communication system with high transmit power and low RSI.The error performance of the FD system is superior to which of the half-duplex system under the same spectral efficiency constraint.The diversity and coding gain can be increased by sufficiently suppressing the self-interference,and the spectral efficiency and power efficiency can be improved as well.